IRON ISOTOPE FRACTIONATION BY FE(II)-OXIDIZING PHOTOAUTOTROPHIC BACTERIA - Croal L.R.; Newman D.K.; Johnson C.M.; Beard B.L. (My University, 2004)
Photoautotrophic bacteria that oxidize ferrous iron (Fe[II]) under anaerobic conditions are thought to be ancient in origin, and the ferric (hydr)oxide mineral products of their metabolism are likely to be preserved in ancient rocks. Here, two enrichment cultures of Fe(II)-oxidizing photoautotrophs and a culture of the genus Thiodictyon were studied with respect to their ability to fractionate Fe isotopes. Fe isotope fractionations produced by both the enrichment cultures and the Thiodictyon culture were relatively constant at early stages of the reaction progress, where the ^(56)Fe/^(54)Fe ratios of poorly crystalline hydrous ferric oxide (HFO) metabolic products were enriched in the heavier isotope relative to aqueous ferrous iron (Fe[II]_(aq)) by ∼1.5 ± 0.2‰. This fractionation appears to be independent of the rate of photoautotrophic Fe(II)-oxidation, and is comparable to that observed for Fe isotope fractionation by dissimilatory Fe(III)-reducing bacteria. Although there remain a number of uncertainties regarding how the overall measured isotopic fractionation is produced, the most likely mechanisms include (1) an equilibrium effect produced by biological ligands, or (2) a kinetic effect produced by precipitation of HFO overlaid upon equilibrium exchange between Fe(II) and Fe(III) species. The fractionation we observe is similar in direction to that measured for abiotic oxidation of Fe(II)_(aq) by molecular oxygen. This suggests that the use of Fe isotopes to identify phototrophic Fe(II)-oxidation in the rock record may only be possible during time periods in Earth’s history when independent evidence exists for low ambient oxygen contents.